Isolation and structural characterization of bioactive compound from Aristolochia sprucei aqueous extract with anti-myotoxic activity - González Rodríguez, Isela I.; Francisco, Aleff F. [UNESP]; Moreira-Dill, Leandro S.; Quintero, Aristides; Guimarães, César L.S.; Fernandes, Carlos A.H. [UNESP]; Takeda, Agnes A.S. [UNESP]; Zanchi, Fernando B.; Caldeira, Cléopatra A.S.; Pereira, Paulo S.; Fontes, Marcos R.M. [UNESP]; Zuliani, Juliana P.; et al. (Elsevier, 2020)
A bioactive compound isolated from the stem extract of Aristolochia sprucei through High Performance Liquid Chromatography (HPLC) was identified via Nuclear Magnetic Resonance (NMR) as the aristolochic acid (AA). This compound showed an inhibitory effect over the myotoxic activity of Bothrops jararacussu and Bothrops asper venoms, being also effective against the indirect hemolytic activity of B. asper venom. Besides, AA also inhibited the myotoxic activity of BthTX-I and MTX-II with an efficiency greater than 60% against both myotoxins. Docking predictions revealed an interesting mechanism, through which the AA displays an interaction profile consistent with its inhibiting abilities, binding to both active and putative sites of svPLA2. Overall, the present findings indicate that AA may bind to critical regions of myotoxic Asp 49 and Lys49-PLA2s from snake venoms, highlighting the relevance of domains comprising the active and putative sites to inhibit these toxins.
Keywords: Antivenom medicinal plants; Aristolochia sprucei; Aristolochic acid; Myotoxin inhibitor; Phospholipases A2; Snake venoms